Tracing microplastics in fish: Uptake, translocation, and multidimensional biological impacts - Yang Yu; Tian-Sheng Zhu; Zi-Yan Liu; Chaowei Song; Zexia Chen; Xiao-Zheng Yu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Hierarchical surface engineering of probiotics for enhanced intestinal retention and colitis therapy - Zongheng Zheng; Yixi Liu; Enguo Ju; Weipeng Zhang; Yuxuan Zhang; Kunjing Wu; Chaowei Zhang; Kangping Sun; Yanteng Xu; Yeh-Hsing Lao; Yu Xu; Xi Xie; et al. (Chemical Engineering Journal, 2026)

Pyrolysis kinetics and mechanism study of walnut shell via Asym2sig deconvolution, Sestak-Berggren reconstruction, and multi-dimensional product analysis - Yuhan Wang; Chaowei Ma; Jianhang Hu; Yong Yu; Cheng Tan; Yuanyuan Duan; Hua Wang (Bioresource Technology, 2026)

Disruption of intestinal mucosal immunity and microbial homeostasis in Schizothorax davidi under chronic DBP exposure: From functional compensation to transcriptional decompensation - Luo Lei; Rongrong Liao; Mei Peng; Yinhua Zhou; Chang Xiao; Xiayu Yu; Shuang Liu; Yuting Duan; Suxing Fu; Hejiao Li; Can Liu; Xiao Chen; et al. (Aquatic Toxicology, 2026)

Cohesion enhancement versus friction degradation: The dual role of nano-SiO 2 in cement-stabilized Dongting Lake sediment - Jie Liu; Hailin Zhang; Chaowei Xue; Xiaowei Yu; Guijin Zhang; Hongyuan Fu (Marine Georesources & Geotechnology, 2026)

Unraveling the Exosome-Derived ceRNA Network of Cartilage Injury in Kashin-Beck Disease Chondrocytes - Chaowei Wang; Lulu Bai; Liangyu Cui; Pengyan Jiao; Zhouyun Chen; Yang Liu; Yirong Qin; Hui Wang; Lian Liu; Qi Jing; Yuyang Ma; Yuequan Yuan; et al. (Biological Trace Element Research, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Construction of a scaffold-mediated dual-enzyme display system in Komagataella phaffii with immobilized cells for continuous biocatalysis - Chaowei Zhou; Fanyu Chen; Jing Leng; Caice Liang; Yu Sha; Wenjun Sun; Huanqing Niu; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Complete genome sequence of a novel carlavirus infecting Passiflora edulis in China - Luping Zheng; Huoyang Ge; Xiaoyue Liu; Shiwei Zhang; Chaowei Yu; Furong Liao; Jianguo Sheng; Ruhui Li (Archives of Virology, 2026)

Cyanobacterial blooms under CO2(aq)-limited conditions in karst reservoirs diminish the synergy of pollution reduction and carbon sequestration via the biological carbon pump - Yunfeng Xue; Cuihong Han; Hailong Sun; Chaowei Lai; Yu Wei; Haibo He (Journal of Hydrology, 2026)

Establishment of a TaqMan qPCR assay for the rapid detection and quantification of Nocardia seriolae in aquaculture - Zexia Chen; Yang Yu; Tiansheng Zhu; Chaowei Song; Zijun Wang; Ziyan Liu; Ran Cai; Lei Luo; Xiangjun Miao; Wensheng Li; Caiyun Sun (Aquaculture, 2026)

Corrigendum to ‘β-Estradiol antagonizes the inhibitory effects of caffeine in BMMSCs via the ERβ-mediated cAMP-dependent PKA pathway’ [Toxicology 394 (2018) 1–10] - Chaowei Wang; Yi Zhou; Xiaoxu Guan; Mengfei Yu; Huiming Wang (Toxicology, 2025)

From attention to action: How public environmental concern shapes corporate green investment in China - Peifeng Wu; Chaowei Zhang; Bowen Yu (Journal of Environmental Management, 2025)

Nitrite exposure on gills of Oreochromis niloticus: structure change, immune response, and apoptosis - Chaowei Song; Tiansheng Zhu; Ran Cai; Yang Yu; Ziyan Liu; Jianing Yan; Yingying Lian; Jiaqi Li; Wensheng Li (Frontiers in Marine Science, 2025)
Nitrite is one of the most common pollutants in high-density aquaculture systems and has a potentially serious impact on the health of fish. The gill, as the organ directly in contact with the environment, performs several vital physiological functions, including gas exchange, osmotic pressure regulation, and mucosal immunity. Using a series of nitrite concentration gradients, we investigated the impact of nitrite on tilapia gills, with a focus on its immune responses. The results indicated that nitrite exposure could significantly increase the number of mucus cells and change the subtypes of chloride cells. Nitrite exposure significantly elevated serum catalase (CAT) activity and decreased superoxide dismutase (SOD) activity. After nitrite treatment, the expression of ion channel protein genes was markedly affected, with a substantial increase in Na + /Cl − cotransporter ( ncc ) expression. Inflammatory gene expression in the gill was also significantly altered. Both in vitro and in vivo experiments revealed that key genes in the IL-17 signaling pathway were considerably altered after nitrite exposure. Mitochondrial damage and apoptosis in the gill tissues were also found after nitrite exposure. In conclusion, nitrite exposure altered immune function and ion transport, especially the activation of the IL-17 signaling pathway, damage to mitochondrial structure, and apoptosis in the gill. This study enhances our understanding of the mechanisms underlying nitrite-induced damage to the gill.

Investigation of the permafrost beneath the subgrade of Qinghai-Tibet railway using electrical resistivity tomography - Yanhui You; Xinbin Wang; Jianglong Dong; Delong Zhang; Zhenyu Zhang; Kun Chen; Lei Guo; Chaowei Wang; Qihao Yu (Engineering Geology, 2025)

Corrigendum to ''β-Estradiol antagonizes the inhibitory effects of caffeine in BMMSCs via the ERβ-mediated cAMP-dependent PKA pathway'' [Toxicology 394 (2018) 1–10] - Chaowei Wang; Yi Zhou; Xiaoxu Guan; Mengfei Yu; Huiming Wang (Toxicology, 2025)

Harmonizing land management strategies with dust transport and water conservation to target of Land Degradation Neutrality in Northern China - Chaowei Zhou; Xiaoming Feng; Yu Zhang; Xuejing Leng; Xiaofeng Wang; Yuan Zhang; Yihe LÜ; Bojie Fu (Journal of Cleaner Production, 2025)

El Niño Southern oscillation events contribute significantly to the interannual variations of dust activity over East Asia - Ruibo Zhao; Xiaoming Feng; Chaowei Zhou; Yu Zhang; Xuejing Leng; Bojie Fu (Atmospheric Research, 2025)

An overview of advancements in biomass pyrolysis modeling: Applications, challenges, and future perspectives in rotary reactors - Chaowei Ma; Ruinan Zhu; Yulei Ma; Yong Yu; Cheng Tan; Shiliang Yang; Huili Liu; Jianhang Hu; Hua Wang (Biomass and Bioenergy, 2025)

Seawater warming rather than acidification profoundly affects coastal geochemical cycling mediated by marine microbiome - Encui Shan; Xiaoli Zhang; Zhenglin Yu; Chaowei Hou; Lei Pang; Shuang Guo; Yongliang Liu; Zhijun Dong; Jianmin Zhao; Qing Wang; Xiutang Yuan (Science of The Total Environment, 2024)

The Impact of Selenium Deficiency and T-2 Toxin on Zip6 Expression in Kashin-Beck Disease - Yifan Wu; Yi Gong; Lian Liu; Lulu Bai; Yu Zhang; Shujin Li; Chaowei Wang; Yuequan Yuan; Xi Lv; Yirong Qin; Hui Wang; Yanli Liu; et al. (Biological Trace Element Research, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Recovery of iron from copper slag using jatropha oil as a green reductant: Investigation of pyrolysis analysis, reaction kinetic and artificial neural network model prediction - Chaowei Ma; Cheng Tan; Yong Yu; Dongfang Li; Jianhang Hu; Hua Wang (Fuel, 2024)

Modulation of Ras signaling pathway by exosome miRNAs in T-2 toxin-induced chondrocyte injury - Chaowei Wang; Minhan Hu; Yuequan Yuan; Xi Lv; Shujin Li; Sijie Chen; Feiyu Zhang; Yifan Wu; Yu Zhang; Yanli Liu; Feihong Chen; Xiong Guo; et al. (Toxicology, 2024)

Control of carbon dioxide exchange fluxes by rainfall and biological carbon pump in karst river–lake systems - Chaowei Lai; Zaihua Liu; Qingchun Yu; Hailong Sun; Fan Xia; Xuejun He; Zhen Ma; Yongqiang Han; Xing Liu; Pengyun Hao; Qian Bao; Mingyu Shao; et al. (Science of The Total Environment, 2024)

Amino acid mutation of succinate dehydrogenase complex induced resistance to benzovindiflupyr in Magnaporthe oryzae - Liyuan Deng; Mengqing Liu; Yang Yu; Yuheng Yang; Anfei Fang; Binnian Tian; Jing Wang; Chaowei Bi (Pesticide Biochemistry and Physiology, 2024)

Genome-wide analysis of R2R3-MYB transcription factors in poplar and functional validation of PagMYB147 in defense against Melampsora magnusiana - Bin Wang; Chaowei Xiong; Zijia Peng; Zeyu Luo; Xiujuan Wang; Shaobing Peng; Zhongdong Yu (Planta, 2024)
Main conclusion Transcription of PagMYB147 was induced in poplar infected by Melampsora magnusiana , and a decline in its expression levels increases the host's susceptibility, whereas its overexpression promotes resistance to rust disease. Abstract Poplars are valuable tree species with diverse industrial and silvicultural applications. The R2R3-MYB subfamily of transcription factors plays a crucial role in response to biotic stresses. However, the functional studies on poplar R2R3-MYB genes in resistance to leaf rust disease are still insufficient. We identified 191 putative R2R3-MYB genes in the Populus trichocarpa genome. A phylogenetic analysis grouped poplar R2R3-MYBs and Arabidopsis R2R3-MYBs into 33 subgroups. We detected 12 tandem duplication events and 148 segmental duplication events, with the latter likely being the main contributor to the expansion of poplar R2R3-MYB genes. The promoter regions of these genes contained numerous cis -acting regulatory elements associated with response to stress and phytohormones. Analyses of RNA-Seq data identified a multiple R2R3-MYB genes response to Melampsora magnusiana ( Mmag ). Among them, PagMYB147 was significantly up-regulated under Mmag inoculation, salicylic acid (SA) and methyl jasmonate (MeJA) treatment, and its encoded product was primarily localized to the cell nucleus. Silencing of PagMYB147 exacerbated the severity of Mmag infection, likely because of decreased reactive oxygen species (ROS) production and phenylalanine ammonia-lyase (PAL) enzyme activity, and up-regulation of genes related to ROS scavenging and down-regulation of genes related to PAL, SA and JA signaling pathway. In contrast, plants overexpressing PagMYB147 showed the opposite ROS accumulation, PAL enzyme activity, SA and JA-related gene expressions, and improved Mmag resistance. Our findings suggest that PagMYB147 acts as a positive regulatory factor, affecting resistance in poplar to Mmag by its involvement in the regulation of ROS homeostasis, SA and JA signaling pathway.

Dust exposure linkages among Asian countries - Chaowei Zhou; Xiaoming Feng; Ruibo Zhao; Yichu Huang; Yu Zhang; Xuejing Leng; Chuanlian Sun; Yihe Lü; Bojie Fu (Journal of Cleaner Production, 2024)

The feedback of greening on local hydrothermal conditions in Northern China - Yu Zhang; Xiaoming Feng; Chaowei Zhou; Ruibo Zhao; Xuejing Leng; Yunqiang Wang; Chuanlian Sun (Science of The Total Environment, 2024)

Imbalance in lake variability but not embodying driving factors on the Qinghai-Tibetan Plateau calls on heterogeneous lake management - Xuejing Leng; Xiaoming Feng; Yu Feng; Chuanlian Sun; Xiaochi Liu; Yu Zhang; Chaowei Zhou; Yunqiang Wang; Bojie Fu (Journal of Environmental Management, 2024)

Field resistance to boscalid and molecular mechanisms of strawberry Botrytis cinerea in Chongqing, China - Pengfei Li; Xueru Yin; Yuheng Yang; Yang Yu; Anfei Fang; Binnian Tian; Chaowei Bi (Australasian Plant Pathology, 2024)

Synergistic activation of persulfate by manganese sulfide and Fe2+: Roles of Fe and enhancement mechanisms - Chaowei Wan; Yu Yang; Jianxin Chen; Yang Wu; Zhifei Ma; Daishe Wu (Journal of Environmental Chemical Engineering, 2023)

Evolution of social-ecological system and the hydrological linkages in oasis area, northwestern China - Yu Zhang; Xiaoming Feng; Chuanlian Sun; Xuejing Leng; Chaowei Zhou; Yunqiang Wang; Bojie Fu (Journal of Arid Environments, 2023)

All-weather precipitable water vapor map reconstruction using data fusion and machine learning-based spatial downscaling - Yongchao Ma; Tong Liu; Zhibin Yu; Chaowei Jiang; Guochang Xu; Zhiping Lu (Atmospheric Research, 2023)

Alleviating eutrophication by reducing the abundance of Cyanophyta due to dissolved inorganic carbon fertilization: Insights from Erhai Lake, China - Chaowei Lai; Zhen Ma; Zaihua Liu; Hailong Sun; Qingchun Yu; Fan Xia; Xuejun He; Qian Bao; Yongqiang Han; Xing Liu; Haibo He (Journal of Environmental Sciences, 2023)

Defective Ru-doped α-MnO2 nanorods enabling efficient hydrazine oxidation for energy-saving hydrogen production via proton exchange membranes at near-neutral pH - Zhipeng Yu; Chaowei Si; Ferran Sabaté; Alec P. LaGrow; Zhixin Tai; Vlad Martin Diaconescu; Laura Simonelli; Lijian Meng; Maria J. Sabater; Bo Li; Lifeng Liu (Chemical Engineering Journal, 2023)

Optimized preparation of gangue waste-based geopolymer adsorbent based on improved response surface methodology for Cd(II) removal from wastewater - Chaowei Dong; Nan Zhou; Jixiong Zhang; Wanan Lai; Jianfei Xu; Junlin Chen; Runhua Yu; Yepeng Che (Environmental Research, 2023)

Monitoring and molecular mechanism of boscalid resistance of Sclerotinia sclerotiorum in Southwest China - Pengfei Li; Furong Peng; Ruixuan Zhang; Yuheng Yang; Yang Yu; Chaowei Bi (Journal of Plant Diseases and Protection, 2022)

Chromosome-Scale Assembly and Characterization of the Albino Northern Snakehead, Channa argus var. (Teleostei: Channidae) Genome - Chaowei Zhou; Yan Li; Yan Zhou; Yu Zou; Dengyue Yuan; Xingxing Deng; Luo Lei; Jian Su; Chengke Zhu; Hua Ye; Hui Luo; Guangjun Lv; et al. (Frontiers in Marine Science, 2022)
Northern snakehead, Channa argus ( C. argus ), is an important economic and ecological fish species. The wild population of the species was sharply declined in the last decade. A high-quality reference genome could lay a solid foundation for the genetic and conservation studies for C. argus . In this work, we report a chromosomal genome assembly with PacBio and Hi-C technology using the albino northern snakehead, a color variety of C. argus . A 644.1-Mb genome with 24 chromosomes was obtained with a contig and scaffold N50 of 11.78 and 27.8 Mb, respectively. We inferred that C. argus diverged from A. testudineus around 85.6 million years ago. 514 expanded gene families and 214 positively selected genes were identified in the C. argus genome. The chromosome-level genome provides a valuable high-quality genomic resource for population, as well as genetic and evolutionary studies for C. argus and other species in Channidae.

The sensitivity of Didymella bryoniae to difenoconazole and boscalid and the synergistic mechanism of fungicide co-formulation - Siyu Liang; Yu Li; Shuntao Liu; Yang Yu; Yuheng Yang; Anfei Fang; Chaowei Bi (European Journal of Plant Pathology, 2021)

Controlling mechanism of absence seizures by deep brain stimulus applied on subthalamic nucleus - Bing Hu; Yu Guo; Xiaoqiang Zou; Jing Dong; Long Pan; Min Yu; Zhejia Yang; Chaowei Zhou; Zhang Cheng; Wanyue Tang; Haochen Sun (Cognitive Neurodynamics, 2018)

Evaluation of resistance of current wheat cultivars and breeding lines to stripe rust from three Gorges reservoir area - Yuheng Yang; Fajing Chen; Dejun Han; Renwu Ruan; Boqun Li; Yang Yu; Chaowei Bi (Journal of General Plant Pathology, 2017)

Characterisation of siRNAs derived from new isolates of bamboo mosaic virus and their associated satellites in infected ma bamboo (Dendrocalamus latiflorus) - Wenwu Lin; Wenkai Yan; Wenting Yang; Chaowei Yu; Huihuang Chen; Wen Zhang; Zujian Wu; Liang Yang; Lianhui Xie (Archives of Virology, 2017)

Molecular characterization and detection of a recombinant isolate of bamboo mosaic virus from China - Wenwu Lin; Fangluan Gao; Wenting Yang; Chaowei Yu; Jie Zhang; Lingli Chen; Zujian Wu; Yau-Heiu Hsu; Lianhui Xie (Archives of Virology, 2016)

Inorganic Composition of Saline-Irrigated Biomass - Peter Thy; Chaowei Yu; Sherry L. Blunk; Bryan M. Jenkins (Water, Air, & Soil Pollution, 2013)